RELATIONSHIP BETWEEN SERUM PROGESTERONE AND ESTRADIOL-17β AND EMBRYONIC LOSS IN FRISIAN COWS UNDER EGYPTIAN CONDITION - ABU EL-HAMD, M A; KADOOM, A K; M FOUAD, W F; HASSOUNA, S H (The Indian Journal of Animal Reproduction, 2022)
Association between circulating progesterone and oestradiol-17β concentrations and embryonic loss in Frisiancows (n=105) under Egyptian condition was investigated. Total embryonic losses in present study were 26.4%.On d25, progesterone (P4) concentrations and sonography revealed 79.3% cows were continuing gestationand 20.7% lost their pregnancies (early embryonic loss, EEL). Furthermore, 7.4% cows with late embryonicloss (LEL) were detected between d25-42. An increase in P4 levels started from day 4 to 7 in cows diagnosedpregnant compared to low P4 in cows that lost pregnancy (p